Occlusal vertical dimension. Review article - Alvítez Temoche, Daniel Augusto (2016)
Modication of occlusal vertical dimension is a procedure that is often necessary for complex oral reha-bilitation treatments to get a functional occlusal for patients. is literature review was made on databases: Medline (PubMed), Scopus, Scielo, BSV (Bireme), ISI (Web of science) and Lilacs using the keywords “occlusal vertical dimension”,”altered vertical dimension”, “temporomandibular joint”, and “masticatory muscles”. It can be said that the management of occlusal vertical dimension is a safe procedure if one takes into account considerations of importance for the prosthetic treatments and all the dental specialties. ere is bibliographic information related to the considerations that should be considered when the occlusal vertical dimension, varies which are applicable in the area of oral rehabilitation.